A DoE-based development and characterization of Nadifloxacin-loaded transethosomal gel for the treatment of Acne vulgaris - Sujeet Patil; Panchaxari M. Dandagi; Taufik Kazi; Sujay Hulyalkar; Prakash Biradar; Vijay Kumbar (SpringerOpen, 2024)
Abstract Background The objective of this current research was to enhance the topical delivery of Nadifloxacin (NDFX) by incorporating it into a transethosomal gel formulation. NDFX has limited penetration into the deep layer of the skin because it is poorly water soluble and it has a log p value of 2.47. To optimize the formulation, the "Box-Behnken design" was utilized. The independent variables included phosphatidylcholine 90, tween 80 and ethanol. The produced formulations underwent evaluation for entrapment efficiency, vesicle size and zeta potential. The optimized formulation was then incorporated into suitable gel bases and subjected to further investigation, including in vitro diffusion, ex vivo penetration, in vitro antimicrobial assay and in vivo anti-acne activity. Results The optimized formulation exhibited an entrapment efficiency of 80.12%, a vesicle size of 156.1 nm and a zeta potential of − 33.23 mV. TEM images confirmed the presence of encapsulated vesicles with a spherical shape. The in vitro diffusion study demonstrated that the transethosomal gel containing Carbopol 934 (1%) exhibited higher drug release compared to the HPMC K4M gels. Furthermore, the ex vivo permeation study revealed that the optimized transethosomal gel demonstrated increased permeation compared to the commercially available formulation. Conclusion The optimized transethosomal formulation displayed enhanced in vitro antimicrobial and in vivo anti-acne effects against Propionibacterium acnes in Wistar albino rats when compared to the marketed formulation.